Measuring the Magnetic Field Using the Zeeman Effect in Nuclear Quadrupole Resonance of GaSe and InSe Compounds - A.P. Samila; G.I. Lastivka; V.O. Khandozhko (Журнал нано- та електронної фізики)
Using pulsed nuclear quadrupole resonance method with a fast Fourier transform of the free induction decay signals, the influence of a weak magnetic field (0 ÷ 10 Gauss) on NQR spectral lines 69Ga and 115In in layered semiconductors GaSe and InSe was investigated. It has been found that the splitting of resonance lines, caused by the Zeeman effect, can be used to determine the magnitude and direction of the applied magnetic field.